Question
upstudy study bank question image url

\( \left. \begin{array} { l } { 2.7 \frac { \sin ( 450 ^ { \circ } - x ) \cdot \tan ( x - 180 ^ { \circ } ) \sin 23 ^ { \circ } \cos 23 ^ { \circ } } { \cos 44 ^ { \circ } \cdot \sin ( - x ) } } \\ { 2.8 \frac { \sin 130 ^ { \circ } \cdot \tan 60 ^ { \circ } } { \cos 540 ^ { \circ } \cdot \tan 230 ^ { \circ } \cdot \sin 400 ^ { \circ } } } \\ { 2.9 \quad \frac { ( 1 - \sqrt { 2 } \sin 75 ^ { \circ } ) ( \sqrt { 2 } \sin 75 ^ { \circ } + 1 ) } { \sin ( 360 ^ { \circ } - x ) \cdot \sin ( 90 ^ { \circ } + x ) } } \\ { 2.10 } \end{array} \right. \)

Ask by Frank Carroll. in South Africa
Feb 28,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

2.7: –½ 2.8: –√3 2.9: (√3)/(sin 2x) 2.10: No expression provided

Solution

We shall simplify the given expressions one‐by‐one. (Note: In the list the item “2.10” does not show any expression to simplify.) ───────────────────────────── 2.7.   Expression:     [sin(450° – x) · tan(x – 180°) · sin 23° · cos 23°]⁄[cos 44° · sin(–x)] Step 1. Write each part in a simpler form.  • sin(450° – x): Notice that 450° = 360° + 90°, so   sin(450° – x) = sin[(360° + 90°) – x] = sin(90° – x) = cos x.  • tan(x – 180°): Since the tangent is 180°‐periodic,   tan(x – 180°) = tan x.  • sin(–x) = – sin x.  • Also recall that sin 23° · cos 23° = (1/2) sin(46°) by the double‐angle formula.  • Finally, note that cos 44° = sin(90° – 44°) = sin(46°). Step 2. Substitute these into the expression:   = [cos x · tan x · sin 23° · cos 23°]⁄[cos 44° · (– sin x)]   = [cos x · (sin x⁄cos x) · sin 23° · cos 23°]⁄[– sin x · cos 44°]   = [sin x · sin 23° · cos 23°]⁄[– sin x · cos 44°]. Step 3. Cancel common factor sin x (assuming sin x ≠ 0):   = [sin 23° · cos 23°]⁄[– cos 44°]. Step 4. Replace the product and the cosine:   = [(1/2) sin 46°]⁄[– sin 46°] = –1/2. Thus, the simplified result for 2.7 is –½. ───────────────────────────── 2.8.   Expression:     [sin 130° · tan 60°]⁄[cos 540° · tan 230° · sin 400°]. Step 1. Rewrite each trigonometric function.  • sin 130°: Since 130° = 180° – 50°, we have sin 130° = sin 50°.  • tan 60° = √3.  • cos 540°: Notice that 540° = 360° + 180° so cos 540° = cos 180° = –1.  • tan 230°: Write 230° = 180° + 50° and use the 180°–periodicity of tangent, so tan 230° = tan 50°.  • sin 400°: Since 400° = 360° + 40°, sin 400° = sin 40°. Step 2. Substitute these:   = [sin 50° · √3]⁄[ (–1) · tan 50° · sin 40°]. Step 3. Write tan 50° as sin 50°⁄cos 50°:   = [sin 50° √3]⁄[– (sin 50°⁄cos 50°) · sin 40°]   = [sin 50° √3 · cos 50°]⁄[– sin 50° · sin 40°]. Step 4. Cancel sin 50° (provided it is nonzero):   = [√3 · cos 50°]⁄[– sin 40°]. Step 5. Notice that cos 50° = sin(90° – 50°) = sin 40°:   = [√3 · sin 40°]⁄[– sin 40°] = –√3. Thus, the simplified result for 2.8 is –√3. ───────────────────────────── 2.9.   Expression:     [(1 – √2 sin 75°)(√2 sin 75° + 1)]⁄[sin(360° – x) · sin(90° + x)]. Step 1. Simplify the numerator. Write it as a product of two conjugates:  Let A = √2 sin 75°. Then   (1 – A)(1 + A) = 1 – A² = 1 – 2 sin² 75°. Step 2. Simplify the denominator.  • sin(360° – x): Using the identity sin(360° – x) = – sin x.  • sin(90° + x) = cos x    (since sin(90° + x) = cos x). Thus, the denominator is (– sin x · cos x) = – (sin x cos x). Step 3. So the expression becomes:   = [1 – 2 sin² 75°]⁄[– sin x cos x]. Step 4. Recognize that 1 – 2 sin²θ = cos 2θ. With θ = 75°, we have:   1 – 2 sin² 75° = cos 150°.  But cos 150° = – cos 30° = – (√3⁄2). Thus, the numerator is –(√3⁄2). Substitute it in:   = [– (√3⁄2)]⁄[– sin x cos x] = (√3⁄2)⁄(sin x cos x). Step 5. Recognize that 2 sin x cos x = sin 2x. Therefore,   (sin x cos x) = (1/2) sin 2x, so   (√3⁄2)/(sin x cos x) = (√3⁄2)/((1/2) sin 2x) = (√3)/(sin 2x). Thus, the simplified result for 2.9 is (√3)/(sin 2x). ───────────────────────────── 2.10.  No expression is given for 2.10 in the problem statement. ───────────────────────────── Summary of Answers:  2.7: –½  2.8: –√3  2.9: (√3)/(sin 2x)  2.10: (No expression provided) These are acceptable simplified forms for the given expressions.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Did you know that trigonometric functions have a rich history dating back to ancient civilizations? The Babylonians and Greeks utilized trigonometry for astronomical calculations, laying the groundwork for modern mathematics. Using angles, they mapped out the heavens, leading to advancements in navigation and understanding of planetary movements. Talk about celestial problem solvers! In today's world, trigonometry is foundational in fields like engineering, physics, and computer graphics. For example, in game development, trigonometric functions help render realistic movements and calculate angles of light, creating immersive experiences. Similarly, architects use these principles to ensure structures are both stable and visually appealing. So, the next time you admire a building or a video game's design, remember the unassuming power of trigonometry at work!

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy